2013
DOI: 10.3109/00016489.2013.829921
|View full text |Cite
|
Sign up to set email alerts
|

Tympanotomy with sealing of the round window as surgical salvage option in sudden idiopathic sensorineural hearing loss

Abstract: A statistically significant improvement in PTA values (mean change 20.4 dB) was noted (p = 0.0002). In all, 13/25 (52%) patients exhibited improved bone conduction postoperatively regardless of age and time of treatment. A marked recovery (≥30 dB) could be seen in eight patients (median time to surgery, 9 days; average age, 48.5 years); recovery between 10 and 30 dB in five patients (median time to surgery, 10 days; average age, 46.6 years). Twelve significantly older patients showed no improvement (average ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Intratympanic triamcinolone-acetonide suspension (applied form verified with the authors) has been used clinically in patients with Ménierè’s syndrome and reported to be a safe and potentially effective procedure for vertigo control (Jumaily et al, 2017). It has also been used as a standard therapy for secondary (salvage) treatment of idiopathic sudden sensorineural hearing loss in some institutions including in one the authors (SKP), (Loader et al 2013, Plontke 2017). Animals treated with dexamethasone or triamcinolone-acetonide delivered intratympanically in hydrogels were found to have reduced inflammation but no significant improvement post-implantation hearing (Honeder et al, 2015).…”
Section: Comparisons Between Drugsmentioning
confidence: 99%
“…Intratympanic triamcinolone-acetonide suspension (applied form verified with the authors) has been used clinically in patients with Ménierè’s syndrome and reported to be a safe and potentially effective procedure for vertigo control (Jumaily et al, 2017). It has also been used as a standard therapy for secondary (salvage) treatment of idiopathic sudden sensorineural hearing loss in some institutions including in one the authors (SKP), (Loader et al 2013, Plontke 2017). Animals treated with dexamethasone or triamcinolone-acetonide delivered intratympanically in hydrogels were found to have reduced inflammation but no significant improvement post-implantation hearing (Honeder et al, 2015).…”
Section: Comparisons Between Drugsmentioning
confidence: 99%
“…A tympanoscopy (middle ear exploration) is a standard otological procedure and has been applied for many years in combination with “sealing” of the RW niche in patients with ISSHL ( Loader et al, 2013 ; Kampfner et al, 2014 ) and for removal of possible RWM obstructions in patients with ISSHL ( Plontke, 2018 ) or with Meniere’s disease ( Crane et al, 2009 ) who have failed therapy with (“blind”) intratympanic injections. All patients in our institution, who this individual treatment attempt was offered to, had quasi lost a sensory organ (complete hearing loss or non-serviceable hearing in the affected ear) and failed other guideline-conform therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute severe to profound sensorineural hearing loss can benefit from treatment with ExT. [3][4][5][6]22 However, as it is an invasive procedure, it should be an ultima ratio when patients do not respond to intravenous and intratympanic cortisone treatment. Our study demonstrates that sealing of the round window membrane during ExT does not impede subsequent CI that remains a viable treatment option when hearing does not recover sufficiently over time.…”
Section: Discussionmentioning
confidence: 99%